Obesity: A Critical Review - SUSMITA BAG; ANANDANBARASU (International Journal of Pharma and Bio Sciences, 2011)
Obesity is a complex interplay of environmental and genetic factors and is associated with significant morbidity and mortality. There are certain detrimental effects to health that are attributed to obesity like metabolic syndrome, cardiovascular disease, diabetes, cancers, high blood pressure. These health consequences associated with obesity result from the cumulative metabolic and physical stress. Obesity is also characterized by an excessively high amount of body fat or adipose tissue. Secretory factors/adipokines released from these adipose tissues undergo abnormal changes with obesity and thus cause a variety of inflammatory conditions. Inherited genetic variation is an important risk factor for obesity and understanding the genetics of obesity will increasingly aid in drug development and better drug targeting to specific patients. This article reviews about factors contributing to obesity, measuring obesity and highlights the need for understanding its prevalence. Also topics on treatment and developing strategies for effective medication are discussed.